2002
DOI: 10.1248/cpb.50.1495
|View full text |Cite
|
Sign up to set email alerts
|

Eudragit NE30D Based Metformin/Gliclazide Extended Release Tablets: Formulation, Characterisation and in Vitro Release Studies.

Abstract: Metformin hydrochloride and Gliclazide are oral hypoglycemic agents 1) belonging to biguanide group and secondgeneration sulphonyl urea respectively. Generally, they are individually used in the treatment of type II non-insulin dependent diabetes mellitus. The combination of both the drugs are also available and it is reported 2) to be effective than individual therapy. Metformin acts 3) by decreasing hepatic glucose production and improves insulin sensitivity by increasing peripheral glucose uptake. Because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A new once daily gliclazide modified release formulation has been recently introduced (12). In a large randomized study on type II diabetic patients, once daily gliclazide modified release 30-120 mg was found as effective as twice daily gliclazide 80-320 mg in reducing glycosylated haemoglobin (HbA1C), with fewer side effects and less risk of hypoglycemia (12)(13)(14)(15). Thus, in this study an attempt was made to prepare oral controlled release mucoadhesive microcapsules of gliclazide utilizing several combinations of mucoadhesive polymers.…”
Section: Introductionmentioning
confidence: 99%
“…A new once daily gliclazide modified release formulation has been recently introduced (12). In a large randomized study on type II diabetic patients, once daily gliclazide modified release 30-120 mg was found as effective as twice daily gliclazide 80-320 mg in reducing glycosylated haemoglobin (HbA1C), with fewer side effects and less risk of hypoglycemia (12)(13)(14)(15). Thus, in this study an attempt was made to prepare oral controlled release mucoadhesive microcapsules of gliclazide utilizing several combinations of mucoadhesive polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Gliclazide, a second generation sulphonyl urea, acts via stimulating β cells of pancreas to release insulin and also increases peripheral sensitivity of insulin [13,14]. In a large randomized study on type II diabetic patients, 30-120 mg once daily dose of Gliclazide was found as effective as 80-320 mg twice daily dose of Gliclazide in reducing glycosylated haemoglobin (HbA1C), with fewer side effects and less risk of hypoglycemia [15][16][17]. Metformin HCl, in particular, increases sensitivity to insulin in peripheral tissues of the hosts.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Relatively Gliclazide is having longer biological half-life (6-15 h) depending upon individual and the dose is 80 mg two-three times a day with meals. Combination of Metformin-500 mg and Gliclazide-80 mg per tablet is available in India and it is to be taken two to three times a day to get required effect [3,4]. Recently, lipid and nonionic surfactant based drug delivery systems specifically niosomes have drawn much attention from researchers as potential carriers of various bioactive molecules that could be used for therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%